Risk factors associated with early adverse outcomes following craniotomy for malignant glioma in older adults. Issue 4 (May 2020) - Rahmani, Redi; Tomlinson, Samuel B.; Santangelo, Gabrielle; Warren, Kwanza T.; Schmidt, Tyler; Walter, Kevin A.; Vates, G. Edward
Abstract: Introduction: Craniotomy for tumor resection improves survival in adults aged ≥65 years with malignant glioma. However, the decision to attempt resection must be weighed against the near-term risks of surgery. This study examined risk factors associated with unfavorable 30-day outcomes following craniotomy for malignant glioma resection in older adult patients. Materials and Methods: The American College of Surgeons National Surgical Quality Improvement Program database from 2012 to 2016 was queried for patients aged 65–89 years undergoing craniotomy for primary, supratentorial, malignant, intra-axial tumor resection. 30-day outcomes included mortality, life-threatening complication, unplanned readmission, reoperation, and change in living disposition. Independent risk factors were identified through multiple logistic regression. Results: In total, 1016 cases met eligibility criteria. Death occurred in 35 cases (3.4%). 58 patients (5.7%) suffered at least one life-threatening complication. Risk factors for morbidity and mortality included frontal lobe tumor, corticosteroid use, dependent functional status, and underweight body mass index (BMI). Among 816 patients admitted from home, 33.9% experienced a change in living disposition, which was associated with advanced age, female sex, frontal lobe tumor, underweight BMI, and diabetes mellitus (among others). Readmission (11.8%) was most frequently attributed to altered mental status, seizure, or venous thromboembolism. Reoperation was rare (4.5%). Discussion: Death and life-threatening morbidity were rare early outcomes for older adult patients undergoing malignant glioma resection. However, one in three patients admitted from home experienced a change in living disposition. Factors related to baseline state of health, tumor location, and corticosteroid regimen should be considered when anticipating the immediate postoperative course.